HAPS (hand, assisting, provide, services) - Mohamad Asri, Muhammad Zarif Hakimi; Shahruddin, Muhammad Houwaidi; Zaidi, Muhammad Nazarul Haziq; Roslan, Muhammad Syazwan; Hassim, Hasniza (Universiti Teknologi MARA, Kedah, 2019)
HAPS is one of the mobile applications which could help all library patrons including the person with differently-abled to reach out the library resources. It is not only used to charging and discharging books, but also to assist the patrons (especially for slow learners) to develop their interest enjoying fun learning atmosphere. We do focuses on providing improved circulation services for charging and discharging items and hence, this application is the most suitable able to be provided as one of the guidance services for the library patrons.